Prevalence of and impact of depression and anxiety on suicidal behaviors among high school students: a cross-sectional survey in five provinces, China - Yan WANG; Chang PENG; Junhan CHENG; Fajuan RONG; Jie HU; Zixuan XU; Meiqi GUAN; Nan ZHANG; Yizhen YU (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo investigate the prevalence of suicidal behaviors, depressive emotion and anxious emotion and the associations of depressive/anxious emotion with suicidal behaviors among high school students in China. MethodsAn on-site self-administered questionnaire survey was conducted among 21 207 students recruited with stratified multistage cluster sampling at 40 high schools in five representative provinces (Jiangsu, Guangdong, Yunnan, Gansu, and Hubei province) of China during April - December 2021. The Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), and a self-designed questionnaire were used to assess the participants' depressive and anxious emotion and to collect demographics and other relevant information of the participants. ResultsOf 20 792 students (10 319 males and 10 473 females aged 11 - 20 years and averagely 15.16 ± 1.87 years) with eligible responses, 23.54% reported ever having suicidal behaviors during past one year, with 10.41%, 8.03%, and 5.10% reporting experience of suicidal ideation, plan, and attempt during past one year, respectively. For all the eligible respondents, the detection rate of depressive and anxious emotion were 19.70% and 13.97% and the highest proportion of having depressive and anxious emotion (27.86% and 19.43%) were detected among rural girl students. The results of multivariate logistic regression analysis showed that compared to urban boy students, both urban and rural girl students were at an increased risk of having suicidal behavior during past one year, with the odds ratio (OR) (95% confidence interval [95% CI]) for urban and rural girl students in terms of suicidal ideation: 1.73 ( 1.52 - 1.97) and 1.68 (1.47 - 1.92), suicidal plan: 1.79 (1.53 - 2.08) and 1.67 (1.43 - 1.95), and suicidal attempt: 1.69 (1.40 - 2.04) and 1.47 (1.22 - 1.78), respectively; the results also revealed significantly positive correlations of depressive and anxious emotion with suicidal behaviors among the students and the correlation of depressive emotion (OR = 5.99, 95% CI: 5.00 - 7.16) and anxious emotion (OR = 3.37, 95% CI: 2.82 - 4.03) were much stronger for suicidal attempt compared to the students without the emotions. ConclusionAmong high school students in China, there are gender and urban-rural differences in the prevalence of suicidal behaviors, depressive/anxious emotion and both depressive and anxious emotion are risk factors of different suicidal behaviors. The study results should be noted in developing relevant intervention measures.